ORGANIZATION OF POLYETHYLENE TEREPHTHALATE PRODUCTION BASED ON LOCAL RAW MATERIALS - Soyibnazarovich, Beknazarov Xasan; o‘g‘li, Karimov Mas’ud Ubaydulla; Rustamovich, To‘rayev Erkin; o‘g‘li, Bekmurodov Azamat Alisher (Research Focus International Scientific Journal, 2026)
Polyethylene terephthalate (PET) is a polymer widely used in various fields due to its excellent physical and chemical properties. However, the ever-increasing use of PET products has led to a global waste management crisis, as the improper disposal of these items has caused serious environmental damage. PET is a primary source of waste accumulating in landfills and methods for its recycling have been developed to address this problem. Accordingly, this review examines various approaches to PET recycling. It discusses traditional recycling methods and the influence of various depolymerization reaction parameters, as well as analyzes the advantages and disadvantages of each method.